DEVELOPMENT OF MENTORING AND APPLICATIONS CONSELING ONLINE (WEB) IN SMA NEGERI 1 BALIKPAPAN - Dydik Kurniawan; Dra. Tri wahyuningsih, M.Si (Peneliti.net, 2018)
The Purpose of This Research is the Development of Guidance and CounselingApplications Online(Web) at SMAN 1 Balikpapan. The research method using descriptive method using the approach of research and development (researchand development).Descriptive research is a research that attempts to clearly describe a phenomenon and event that occurs now, which means focusing on actual problems as they were at the time the research was conducted. Based on the research method used, namely research and development, the procedures that can be taken include the following steps: Stage, Data Collection Phase, Data Processing and Analysis Phase, Designing Phase, Validation, and Model Revision, Limited Test Phase and Revision Phase . Guidance and counseling services in SMAN 1 are not yet fully optimal, because there are limitations of time and place, so service delivery has so far been focused on students who have problems. There are still many students who have never come to the BK room, they feel awkward when visiting the BK room, and often get obstacles when consulting.